DIVERSION TRANSPORTATION TIME INTO QUALITY TIME DURING COVID-19 PANDEMIC - Fauzan Ferdiansyah; Fitra Faturachman; Listiowatty; Aan Hartati; Hendro Prabowo (Jurnal Transportasi, 2022)
Abstract The Covid-19 pandemic has become a major problem in the world in recent years, and has changed the way people live in many aspects. Many activities, rules, habits, and norms, that were carried out previously, turned into new habits. The impact of the Covid-19 pandemic, that is felt by people in Indonesia, comes from the Government's policies on physical and social distancing, such as limiting activities outside the home, closing school activities, and working from home. As a result, many work activities were conducted at home online rather than in the office. This condition makes employees have to adapt to the pattern of working remotely from their respective homes. This study aims to explore the activities they do with the transportation time they used previously, using a sample of several people who live in Jabodetabek and work as teachers, employees, and students. This study shows that those who do their activities from home use the time that should have been used to travel from home to work and vice versa, for more quality things, both for themselves and for their families. Keywords: Covid-19 pandemic; work from home; work activities; transportation time. Abstrak Pandemi Covid-19 telah menjadi masalah besar di dunia dalam beberapa tahun terakhir, dan telah mengubah cara hidup masyarakat dalam banyak aspek. Banyak kegiatan, aturan, kebiasaan, dan norma yang dilakukan sebelumnya berubah menjadi kebiasaan-kebiasaan baru. Dampak pandemi Covid-19 yang dirasakan masyarakat di Indonesia berasal dari kebijakan Pemerintah tentang physical dan social distancing, seperti membatasi aktivitas di luar rumah, meliburkan aktivitas sekolah, dan work from home. Akibatnya, Banyak aktivitas kerja yang dilakukan di rumah secara online daripada dilakukan di kantor. Kondisi ini membuat karyawan harus beradaptasi dengan pola kerja jarak jauh dari rumah masing-masing. Studi ini bertujuan untuk mengeksplorasi kegiatan yang mereka lakukan dengan waktu transportasi yang mereka gunakan sebelumnya, dengan menggunakan sampel beberapa orang yang tinggal di Jabodetabek dan berprofesi sebagai guru, karyawan, dan mahasiswa. Studi ini menunjukkan bahwa mereka yang melakukan aktivitasnya dari rumah memanfaatkan waktu yang seharusnya digunakan untuk melakukan perjalanan dari rumah ke kantor dan sebaliknya, untuk hal-hal yang lebih berkualitas, baik untuk mereka sendiri maupun untuk keluarga mereka. Kata-kata kunci: pandemi Covid-19; work from home; aktivitas kerja; waktu transportasi.